Repulsion to Ritual: Interpreting Folk Festivals in the Polish Tatras - Cooley, Timothy (Ethnologies, 2001)
Folklore festivals and other presentations of folk music for tourists are frequently interpreted as pale representations of “real” folk music at best, and commercial corruptions at worst. The author at least has been guilty of such interpretations. In this article, he interprets folklore festivals in southern Poland as highly meaningful calendric rituals necessary for the survival of certain ways of life. Folklore festivals replace, sometimes quite deliberately, more commonly recognised calendric rituals formerly enacted to preserve agricultural livelihood. One thing preserved and protected by the folklore festival ritual is the concept of “authentic folk music.” Once the protective ritual is performed, the participants are free to go and engage in other “non-authentic” music activities. The author shows how these notions of authenticity and preservation are negotiated by performers, festival promoters, local musical folklorists, and tourists. Rather than being repulsed by the inevitable changes in “back-region” performance practices for stylised “front-region” staged performances, he views them as meaningful responses to changing social, economic and cultural conditions.